HYDROLYSIS OF WHEAT STRAW HEMICELLULOSE AND DETOXIFICATION OF THE HYDROLYSATE FOR XYLITOL PRODUCTION - Junping Zhuang; Ying Liu; Zhen Wu; Yong Sun; Lu Lin (BioResources, 2009)
Xylitol can be obtained from wheat straw hemicellulose containing a high content of xylan. This study describes a new system of hydrolysis, utilizing a mixed solution of formic acid and hydrochloric acid in which xylan can be hydrolyzed effectively. The hydrolysate contains a high content of formic acid, which markedly inhibits the fermentation. One of the most efficient methods for removing inhibiting compounds is treatment of the hydrolysate with ion-exchange resins. Formate can be removed by a factor of 77.78%, and furfural, acetic acid, phenolic compounds can be removed by 90.36%, 96.29%, and 77.44%, respectively after the hydrolysate has been treated with excess Ca(OH)2 and D311 ion-exchange resin. The xylose from the hydrolysis process can be fermented by Candida tropicalis strain (AS2.1776) to produce xylitol with a yield of 41.88 % (xylitol/xylose).